PEMANFAATAN PASIR PUTIH SEBAGAI BAHAN PEMBUATAN BETON MUTU TINGGI - Abdi NAsrullah; Edowinsyah (JURNAL ILMIAH BERING'S, 2022)
This study aims to determine the effect of white sand on high-strength concrete in this case the quality of 26 MPa concrete. The method used in this research is direct testing in the laboratory. The test object is made in the form of a cube with a size of 15 x 15 x 15 cm. As many as 20 specimens were made, the compressive strength of the concrete was tested at the age of 3,7,14,21 and 28 days, the cement used was PCC cement. Testing / testing includes the compressive strength of concrete. The stage of mixing or stirring between cement, sand, and water. done homogeneously. From the results of the study, the average compressive strength value of 28 days of concrete was obtained. Concrete using fine white sand aggregate obtained a compressive strength value of ; 35,5 MPa.